Costly Labour Adjustment: General Equilibrium Effects of China's Employment Regulations and Financial Reforms. (17th November 2017) - Cooper, Russell; Gong, Guan; Yan, Ping
Abstract : This article studies the employment and productivity implications of new Chinese labour regulations. We estimate a general equilibrium model of costly labour adjustment from data prior to the policy to study the effects of the interventions. Increases in severance payments are particularly effective and lead to sizable private sector responses. If in place at the time, these frictions would have reduced China's annual growth rate by nearly 1 percentage point between 1998 and 2007, a period of intense privatisation. Credit market liberalisation reduces private firm size and increases private sector employment, labour reallocation, wages and output.